2015
DOI: 10.2147/ott.s73366
|View full text |Cite
|
Sign up to set email alerts
|

High mobility group box-1 and its clinical value in breast cancer

Abstract: BackgroundHigh mobility group box-1 (HMGB1) is a factor regulating malignant tumorigenesis, proliferation, and metastasis, and is associated with poor clinical pathology in various human cancers. We investigated the differential concentrations of HMGB1 in tissues and sera, and their clinical value for diagnosis in patients with breast cancer, benign breast disease, and healthy individuals.MethodsHMGB1 levels in tumor tissues, adjacent normal tissues, and benign breast disease tissues was detected via immunohis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 36 publications
1
19
1
Order By: Relevance
“…The genes MAPK3 , HMGB1 , HMGA1 , PIK3CA , and MCL1 are genes known to stimulate cellular growth; however, contrary to what is normally reported in humans [ 46 , 47 , 48 , 49 , 50 ], in the present study these genes were shown to be consistently expressed at lower levels in malignant tumors. Therefore, it is hypothesized that those genes play a different role in canine mammary tumors.…”
Section: Discussioncontrasting
confidence: 98%
“…The genes MAPK3 , HMGB1 , HMGA1 , PIK3CA , and MCL1 are genes known to stimulate cellular growth; however, contrary to what is normally reported in humans [ 46 , 47 , 48 , 49 , 50 ], in the present study these genes were shown to be consistently expressed at lower levels in malignant tumors. Therefore, it is hypothesized that those genes play a different role in canine mammary tumors.…”
Section: Discussioncontrasting
confidence: 98%
“…Several studies report that HMGB1 plays a key role in various types of malignancies, such as breast cancer [ 40 ], gastric cancer [ 41 ] and hepatocellular carcinoma [ 42 ]. However, certain factors remain unclear that are related to the overexpression and prognosis of HMGB1 in NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…HMGB1 is highly expressed in most tumor types. Previous studies found that the expression of HMGB1 was much higher in tumor than in the normal tissue counterpart, such as hepatocellular carcinoma [ 15 ], breast carcinomas [ 43 ] and colorectal adenocarcinomas [ 44 ]. However, certain cancers such as adrenal gland carcinoma contain no HMGB1 protein [ 38 ].…”
Section: The Biology Of Hmgb1mentioning
confidence: 99%